Research advancements in smart technology, optimization, and renewable energy - Vasant, Pandian; Weber, Gerhard 1960-; Punurai, Wonsiri 1979- (IGI Global, 2020)
"This book explores the recent steps forward for smart applications in sustainability"--
Description based on title screen (IGI Global, viewed 08/08/2020)
Keywords: Artificial intelligence / Industrial applications; Electric power systems; Machine learning; Renewable energy sources; Smart materials; Technological innovations; Wearable technology